Tubewell platform color: Assessment of a tool for rapid screening of arsenic and manganese in well water - Bhattacharya, P.; Biswas, A.; Halder, D.; Jacks, G.; Nath, B.; Biswas, A.; Halder, D.; Chatterjee, D.; Mukherjee, Abhijit (2012)
This study attempts to make a statistical comparison between Tubewell (TW) platform color and the level of Arsenic (As) and Manganese (Mn) concentration in groundwater abstracted from a set of 423 Tubewells (TWs) in Chakdaha Block of Nadia District, West Bengal, India to validate platform color as a screening tool for both As and Mn in groundwater. The results indicate that water extracted from TWs with black colored platform in 93% cases was safe for As while water extracted from TWs with red colored platform is contaminated with As with 38% certainty, compared to drinking water standard of India (50 µg/L). At this standard the respective efficiency, sensitivity and specificity of the tool are 65, 85 and 59%. If WHO drinking water guideline (10 µg/L) is considered, the certainty increases to 73% and 84% respectively for black and red colored platform with respective efficiency, sensitivity and specificity values of 79, 77 and 81%. Furthermore, the black colored platform with 78% certainty indicates well water is enriched with Manganese (Mn), while red colored platform indicates water is low in Mn with 64% certainty evaluated against Indian national standard of 300 µg/L. This study demonstrates that platform color can be potentially used as an initial screening tool for As and Mn, to assess the safe water acess for drinking purposes. © 2012 Taylor & Francis Group.